1997
DOI: 10.1159/000276901
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Performance with the COMBI 40 Cochlear Implant in Adults: A Multicentric Clinical Study

Abstract: The present multicentric clinical study involves 19 centres, 16 of them in German-speaking countries, 1 British, 1 Polish and 1 Hungarian. 60 postlingually deafened adults with a mean age of 47.5 years (20–70) and a mean duration of deafness of 5.3 years (0.5–20) have been evaluated with the MED-EL COMBI 40 cochlear implant which implements a high-rate continuous-interleaved-sampling strategy with 8 channels. Safety and effectiveness data have been collected. Speech perception tests include a 16-consonant, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 2 publications
4
70
0
3
Order By: Relevance
“…The solid line in each panel shows the mean of the individual scores. The data are a superset of those reported in Helms et al (1997), that include scores for additional subjects at various test intervals, as reported in Wilson (2006). Most of the subjects used an 8-channel processor with a pulse rate of about 1500/s/electrode.…”
Section: Performance With Present-day Unilateral Implantsmentioning
confidence: 93%
“…The solid line in each panel shows the mean of the individual scores. The data are a superset of those reported in Helms et al (1997), that include scores for additional subjects at various test intervals, as reported in Wilson (2006). Most of the subjects used an 8-channel processor with a pulse rate of about 1500/s/electrode.…”
Section: Performance With Present-day Unilateral Implantsmentioning
confidence: 93%
“…A number of cochlear implant centers have reported several cases of hearing preservation and have demonstrated that patients can integrate acoustically and electrically stimulated percepts (Gantz et al, 2005;Gantz & Turner, 2004;Gstoettner et al, 2004;Kiefer et al, 2005;Skarzynski, Lorens, & Piotrowska, 2004;von Ilberg et al, 1999). The mean monosyllabic word recognition scores of EAS listeners have been reported to be as high as 79% (Gantz et al, 2005)-much higher than the mean score of 55%-60% correct reported for conventional, unilateral cochlear implants (Helms et al, 1997).…”
Section: Combined Electric and Acoustic Stimulation (Eas)mentioning
confidence: 93%
“…Scores for the Hochmair-Schultz-Moser sentences are presented in Figure 8(a), and scores for recognition of the Freiburger monosyllabic words are [57] and include scores for additional subjects at various test intervals. Most of the subjects used an eight-channel processor with a pulse rate of about 1,500/s/electrode.…”
Section: Performance With Present-day Systems Average Performance Andmentioning
confidence: 99%
“…Scores for the electric-only condition are shown in the middle column, and scores for the combined EAS condition are shown in the right column. In addition, scores for the 55 subjects in the Helms et al study [57] are shown in the left column to provide a reference for findings with a fully inserted cochlear implant from a large population of tested subjects. (These data are the same as those presented in the rightmost column of Figure 8(b).…”
Section: Recent Advancesmentioning
confidence: 99%